2021
DOI: 10.1016/j.ajoc.2021.101200
|View full text |Cite
|
Sign up to set email alerts
|

Acute macular neuroretinopathy following Pfizer-BioNTech COVID-19 vaccination

Abstract: Purpose To describe a case of acute macular neuroretinopathy (AMN) in a patient immediately following administration of the Pfizer-BioNTech COVID-19 vaccine. Observations The patient complained of paracentral scotoma supported by paracentral visual field loss on multiple Humphrey visual fields that corresponded to outer retinal pathology on optical coherence tomography. The patient's symptoms resolved without treatment. Conclusions and Importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…Near-infrared imaging and OCT imaging confirmed a diagnosis of bilateral AMN. Valenzuela et al described a similar report of bilateral AMN following vaccination with the second dose BNT162b2 vaccine [93]. In contrast to other reports, the authors reported resolution of symptoms after 7 days with observation only.…”
Section: Acute Macular Neuroretinopathymentioning
confidence: 88%
“…Near-infrared imaging and OCT imaging confirmed a diagnosis of bilateral AMN. Valenzuela et al described a similar report of bilateral AMN following vaccination with the second dose BNT162b2 vaccine [93]. In contrast to other reports, the authors reported resolution of symptoms after 7 days with observation only.…”
Section: Acute Macular Neuroretinopathymentioning
confidence: 88%
“…Cases of AMN after COVID vaccination and influenza vaccination were recently reported and strengthen a possible association between AMN and vaccination. 5 , 8 , 9 , 10 , 11 , 12 Although the pathogenesis of AMN remains uncertain and complex, a retinal microvascular etiology affecting the deep retinal capillary plexus (DCP) is suggested. 6 , 8 It is plausible that relative hypovolemia associated with fever and flu-like illness post-vaccination or possibly subclinical small deep retinal capillary vasculitis leading to ischemia of the DCP.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects received the AZD1222 vaccine. In another case report, Valenzuela et al reported a case of a young female subject who presented with bilateral scotoma and photopsia 48 h after receiving the second dose of the BNT162b2 vaccine [ 46 ]. The subject was using an etonogestrel/ethinyl estradiol 0.12–0.015 mg/24 h vaginal ring for birth control.…”
Section: Covid-19 Vaccine-associated Ocular Inflammationmentioning
confidence: 99%